LAW AND MORAL JUSTIFICATION (Revista Kriterion, 2020)
Many prominent legal philosophers believe that law makes some type of moral claim in virtue of its nature. Although the law is not an intelligent agent, the attribution of a claim to law does not need to be as mysterious as some theorists believe. It means that law-making and law-applying acts are intelligible only in the light of a certain presupposition, even if a lawmaker or a law-applier subjectively disbelieves the content of that presupposition. In this paper, I aim to clarify what type of moral claim would be suitable for law if law were to make a claim to be morally justified. I then argue that legal practice is perfectly intelligible without moral presuppositions – that is, that the law does not necessarily make moral claims